Latin Super, Hittite Šer, and the Indo-European Numeral ‘7’ - Shields, Kenneth (Lingua Posnaniensis, 2011)
In this brief paper, it is argued that the initial *s- found in the Latin and perhaps Greek reflexes of the Indo-European adprep *uper(i) ‘over, above’ derives from blending with another adprep of the same meaning, *ser(i). Evidence is also presented for the creation of another blend involving these two forms, *sep-, which may underlie the Indo-European root for ‘7’. This latter assertion is strengthened by typological precedent.